Analisis Kualitas Website dengan Menggunakan Metode Webqual 4.0 dan Importance Performance Analysis - Romlih Romlih; Cahyani Budihartanti (Journal of Information System Research (JOSH), 2023)
The development of technology, information and communication (TIK) is growing very rapidly and dynamically. Www.rsuppersahabatan.co.id, is a website owned by the government in the health sector provided by the Friendship Hospital as a form of service to the community in providing information and health services online. As a national respiratory referral center hospital and has a vision as a world-level hospital that has excellent respiratory services. Of course, many users access the website to seek information related to health service needs, training, education and research in the health and medical fields. Of course this is a challenge for Persahabatan Hospital to improve the quality of the website so that it can compete not at the national level but at the world level. The purpose of this study was to measure user satisfaction with the service quality of the Persahabatan Hospital website. The instrument used in this study was a questionnaire with a simple random sampling technique. In this study, the methods used were webqual and IPA methods. The webqual method consists of aspects of usability, information quality and interaction quality. The IPA method is used to analyze the level of suitability and gaps based on the level of satisfaction and expectations of the users.The results of calculating the IPA method can be described by the IPA matrix which consists of four quadrants. From the results of the analysis in this study, the largest gap (gap) is in the aspect of information quality with an average value of 0.41%.